2023
DOI: 10.1021/acs.jctc.2c00788
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy from Machine Learning by Accurately Representing the Atomic Polar Tensor

Abstract: Vibrational spectroscopy is a key technique to elucidate microscopic structure and dynamics. Without the aid of theoretical approaches, it is, however, often difficult to understand such spectra at a microscopic level. Ab initio molecular dynamics has repeatedly proved to be suitable for this purpose; however, the computational cost can be daunting. Here, the E(3)-equivariant neural network is used to fit the atomic polar tensor of liquid water a posteriori on top of existing molecular dynamics simulations. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…We exploit equivariant (invariant and covariant to the SO(3) group symmetry operations) atom-centred ML models 72,73 that bypass niteelectric eld electronic structure calculation and respect the physical symmetries of the rank-1 polarization and rank-2 polarizability tensors. We, amongst others, have combined equivariant ML of total polarization and polarizability tensors with classical or PI quantum dynamics methods to predict liquid water IR 17,74,75 and Raman spectra. 17,18,22 A hurdle towards rst-principles SFG modelling is that its computable expressions are written in terms of molecular polarization and polarizability tensors, which are ill-dened in rst-principles modelling.…”
Section: Equivariant ML Models Of Dielectric Responses With Non-condo...mentioning
confidence: 99%
“…We exploit equivariant (invariant and covariant to the SO(3) group symmetry operations) atom-centred ML models 72,73 that bypass niteelectric eld electronic structure calculation and respect the physical symmetries of the rank-1 polarization and rank-2 polarizability tensors. We, amongst others, have combined equivariant ML of total polarization and polarizability tensors with classical or PI quantum dynamics methods to predict liquid water IR 17,74,75 and Raman spectra. 17,18,22 A hurdle towards rst-principles SFG modelling is that its computable expressions are written in terms of molecular polarization and polarizability tensors, which are ill-dened in rst-principles modelling.…”
Section: Equivariant ML Models Of Dielectric Responses With Non-condo...mentioning
confidence: 99%
“…The field of machine learning (ML) within computational chemistry has grown very rapidly in the past decade. 8 Application examples are found in various areas, such as molecular property prediction, 9 crystal structure determination via NMR chemical shifts, 10 prediction of vibrational spectra, 11 and a complete general density functional approximation (DM21). 12 Since quantum-chemistry-based methods for predicting NMR parameters can have serious drawbacks, such as insufficient accuracy or high computational cost (depending on the systems of interest), the use of artificial neural networks (ANN) and machine learning for this purpose has become increasingly popular in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) techniques are being increasingly applied to various areas of theoretical and computational chemistry given their ability to infer structure–property relationships on the basis of large amounts of data. Among those ML techniques, graph neural networks (GNN) and deep neural networks (DNN) are promising candidates to predict the properties of matter, such as the electronic structure, at a higher computational speed, already making them favorable for high-throughput calculations in materials design and drug discovery. , Thus, the ability to perform efficient computations with high accuracy has demonstrated that ML techniques are advantageous in domains such as various types of spectroscopy, including vibrational and optical. , …”
Section: Introductionmentioning
confidence: 99%